CHARACTERIZATION AND STRENGTH ANALYSIS OF REINFORCED BAMBOOS AND BAMBOOS WITHOUT REINFORCEMENTS - L, Gyansah; I.A, Adetunde (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
This paper investigates the strength of reinforced fresh, reinforced dried and bambooswithout reinforcement subjected to static loading condition. Crushing strength test wasperformed using uniaxial compression machine with maximum loading capacity of1500 KN. The data is plotted as failure stress to height, specific compressive strengthwith height, strength to weight ratio versus height, strength to volume ratio versusheight. Result shows that the strength increases as the height increases for all structuresanalysed. All the bamboo structures exhibited elastic behaviour, but the reinforced freshbamboo showed higher elastic behavior to the transition point. The dried reinforcedbamboo proves to have the highest intrinsic strength beyond the transition point. Failurestress to weight ratio also decreases with increases with height for all cases of thestructures. The specific compressive strength of both non-reinforced fresh and dried hasan appreciable increased up to a transition point and then it decreased with increasedwith height. Failure stress proves that the strength of reinforced dried bamboo increaseswith increases in height. Conclusively, the reinforced dried bamboo can withstandhigher compressive load than the rest of the bamboo structures